A previously undescribed syndrome of thoracic dysplasia and communicating hydrocephalus in two sibs, one diagnosed prenatally by ultrasound. Issue 4 (April 1987) - Winter, R M; Campbell, S; Wigglesworth, J S; Nevrkla, E J
Abstract : We describe two opposite sexed sibs, the offspring of consanguineous Pakistani parents, with a previously undescribed syndrome. The main features are short ribs with a narrow chest and thoracic dysplasia, mild shortening of the limbs, communicating hydrocephalus, and developmental delay. One sib was diagnosed prenatally by ultrasound at 18 weeks' gestation. The inheritance of the condition is presumed to be autosomal recessive.